Stress-strain and absorption of lightweight concrete with artificial lightweight aggregate from diatomaceous earth. Issue 1 (February 2021) - Hasan, M; Putra, R; Saidi, T; Jamil, M; Husna, N; Syukranlillah, M
Abstract: Lightweight concrete can be produced by using artificial lightweight aggregate (ALWA). Diatomaceous earth has extremely low density therefore can be used as a raw material to make ALWA. It is important to understand a stress-strain relationship of materials before they can be used as structural members. This paper presents the stress-strain of lightweight concrete with ALWA from diatomaceous earth based on the experimental observation. In addition, the relationship between the absorption of the lightweight concrete and the immersion time is also presented. Two types of ALWA were produced which are the ALWA made of diatomaceous earth only and the ALWA with the addition of 5% sawdust. A polynomial model of the stress-strain curve was proposed for lightweight concrete containing a different type of ALWA. The absorption of lightweight concrete with ALWA containing sawdust was higher than that of diatomaceous earth only.